Nghiên cứu công nghệ chế tạo và hoạt tính xúc tác của nano vàng trên chất mang Fe2O3 - Tráng, Nguyễn Công; Minh Nguyệt, Trần Thị; Huấn, Nguyễn Quang; Nghiễm, Lại Xuân; Thái, Nguyễn Doãn; Chân, Đỗ Thế; Chi, Trần Quế; Trung, Nguyễn Quốc (Vietnam Journal of Chemistry, 2014)
Au/Fe2O3catalyst was prepared by the coprecipitation method. The formation process of Au/Fe2O3was investigated by DTA, TGA, DrTGA, TEM, HRTEM and XRD. The results show that the gold particle size of the sample calcined at 300oCis in the range 1.2 - 7.8 nm. The catalytic oxidation of CO and H2was determined